Life‐history genomic regions explain differences in Atlantic salmon marine diet specialization. Issue 11 (28th September 2020) - Aykanat, Tutku; Rasmussen, Martin; Ozerov, Mikhail; Niemelä, Eero; Paulin, Lars; Vähä, Juha‐Pekka; Hindar, Kjetil; Wennevik, Vidar; Pedersen, Torstein; Svenning, Martin‐A.; Primmer, Craig R.
Abstract: Animals employ various foraging strategies along their ontogeny to acquire energy, and with varying degree of efficiencies, to support growth, maturation and subsequent reproduction events. Individuals that can efficiently acquire energy early are more likely to mature at an earlier age, as a result of faster energy gain which can fuel maturation and reproduction. We aimed to test the hypothesis that heritable resource acquisition variation that covaries with efficiency along the ontogeny would influence maturation timing of individuals. To test this hypothesis, we utilized Atlantic salmon as a model which exhibits a simple, hence trackable, genetic control of maturation age. We then monitored the variation in diet acquisition (quantified as stomach fullness and composition) of individuals with different ages, and linked it with genomic regions (haploblocks) that were previously identified to be associated with age‐at‐maturity. Consistent with the hypothesis, we demonstrated that one of the life‐history genomic regions tested (s ix6 ) was indeed associated with age‐dependent differences in stomach fullness. Prey composition was marginally linked to six6, and suggestively (but non‐significantly) to vgll3 genomic regions. We further showed Atlantic salmon switched to the so‐called 'feast and famine' strategy along the ontogeny, where older age groups exhibited heavier stomach content, but that came at the expense of running on empty more often. These results suggest genetic variation underlying resource utilization may explain the genetic basis of age structure in Atlantic salmon. Given that ontogenetic diet has a genetic component and the strong spatial diversity associated with these genomic regions, we predict populations with diverse maturation age will have diverse evolutionary responses to future changes in marine food web structures. Abstract : Individuals exhibit variation in diet acquisition efficiency along the ontogeny. Aykanat et al. postulated that heritable ontogenetic diet variation may explain differences in maturation timing. Using Atlantic salmon, which have simple genetic control of maturation age, and consistent with the hypothesis, they demonstrated that these genomic regions linked to age‐dependent resource utilization variation.